Analysis of the movement form of the five-pointed nyireh dance from Muara Enim, South Sumatra - Tiara Wulandari (Yayasan Baru Haji Samsudin, 2024)
The Muara Enim Welcome Dance is a dance that lives and develops in Muara Enim Regency, South Sumatra, before the welcoming dance was called the Sembah Dance which grew and developed in the hamlet community of Muara Enim Regency. No one knows who created this Sembah Dance because this Traditional Dance is the culture and art of the Kikim ethnic community around 400 years ago. The dance which is included in the elements of this art originates from oral stories passed down from generation to generation based on the experiences of previous ancestors. More or less around 1956, the Prayer Dance was initiated again by Mr. M. Natar. Research This study aims to analyze the Welcome Dance of Muara Enim in developing the Nyireh Lima Berintit Dance in the Muara Enim community. The Nyireh Lima Berintit dance is a dance that is performed at welcoming important guests and weddings, this dance is developed to be 10 minutes. This dance is always danced by 5 female dancers and accompanied by 3 male dancers holding umbrellas and spears standing behind the female dancers. In this study using Y. Sumandiyo Hadi's theory which contains an analysis of the forms of motion, the benefits of this research are to identify and study and analyze the problems that arise in the development of this dance. So this research uses a qualitative approach by focusing on data collection.